Niche induced cell death and epithelial phagocytosis regulate hair follicle stem cell pool - Mesa, Kailin R. (Nature, 2015)
Tissue homeostasis is achieved through a balance of cell production (growth) and elimination (regression)(1,2). Contrary to tissue growth, the cells and molecular signals required for tissue regression remain unknown. To investigate physiological tissue regression, we use the mouse hair follicle, which cycles stereotypically between phases of growth and regression while maintaining a pool of stem cells to perpetuate tissue regeneration(3). Here we show by intravital microscopy in live mice(4–6) that the regression phase eliminates the majority of the epithelial cells by two distinct mechanisms: terminal differentiation of suprabasal cells and a spatial gradient of apoptosis of basal cells. Furthermore, we demonstrate that basal epithelial cells collectively act as phagocytes to clear dying epithelial neighbors. Through cellular and genetic ablation we show that epithelial cell death is extrinsically induced through TGFβ activation and mesenchymal crosstalk. Strikingly, our data show that regression acts to reduce the stem cell pool as inhibition of regression results in excess basal epithelial cells with regenerative abilities. This study identifies the cellular behaviors and molecular mechanisms of regression that counterbalance growth to maintain tissue homeostasis.